Ответ:
(см. объяснение)
Пошаговое объяснение:
Просто подставь значения x и y в данное уравнение.
- 3 + 9 - 6 = 0 \\ 0 = 0" alt="2x + 3y - 6 = 0 \\ \\ x = - 1.5 \\ y = 3 \\ \\ = > - 3 + 9 - 6 = 0 \\ 0 = 0" align="absmiddle" class="latex-formula">
Пункт 3 доказан.
![2 \times 9 + 3 \times ( - 4) - 6 = 0 \\ 18 - 12 - 6 = 0 \\ 0 = 0 2 \times 9 + 3 \times ( - 4) - 6 = 0 \\ 18 - 12 - 6 = 0 \\ 0 = 0](https://tex.z-dn.net/?f=2%20%5Ctimes%209%20%2B%203%20%5Ctimes%20%28%20-%204%29%20-%206%20%3D%200%20%5C%5C%2018%20-%2012%20-%206%20%3D%200%20%5C%5C%200%20%3D%200)
Пункт 4 доказан.